Challenges of Sharia Banking Notaries in Indonesia's Economic Development in the Global Era - Ro’fah Setyowati; Bagas Heradhyaksa (Procedia of Social Sciences and Humanities, 2021)
Notaries have a strategic position in making Islamic banking contracts. The reason is that the notary is responsible for the correctness of the contract construction to fulfill the terms of the agreement and the sharia principles. This study aims to find the philosophy of juridical consequences of the notary profession relationship with Islamic banking, which is associated with challenges in the global era. This research uses a philosophical, juridical, and empirical approach. The analysis results show that a notary who has sharia competence and understands and also carries out the philosophy of juridical consequences of the profession is very much needed. This is due to the growing challenges in developing Islamic banking globally, particularly about competition due to advances in information technology